(untitled) (Biocenosis, 2021)
The article describes the construction process of an aquatic mesocosm as a strategy for pedagogical mediation that reinforces six learning skills (critical thinking, systems thinking, problem solving, creativity and innovation, collaboration, and communication). These skills make up an integral part of the Pedagogical Foundation for Curricular Transformation, presented by the Public Education Ministry of Costa Rica in 2015, which has been designed with the objective of generating changes in the mediation, evaluation and participation processes for teachers and students in various educational settings. In response to these changes, the strategy called Learning Skills Development from the Creation of a Mesocosm, is proposed, which is based on the construction, observation and systematization of the various biological processes that take place in a self-sustaining ecosystem. It is worth noting that the achievement level for the six learning skills is evaluated, through data systematization tables and rubrics.